An Empirical Study on the Influencing Factors and Promotion Strategies of College Students’ Physical Exercise Behaviour Based on Social Cognitive Theory - Wenbo Li; Yi Zhang; Hasmadi Bin Hassan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This study examines the key factors influencing college students' engagement in physical exercise and proposes relevant strategies for promotion, grounded in Social Cognitive Theory (SCT). A survey of 500 college students was conducted, with the data analysed using Structural Equation Modelling (SEM). The findings reveal that self-efficacy, social support, and environmental factors exert a significant influence on students' physical exercise behaviours. Moreover, the study identifies attitudes and intentions as mediators in the relationship between self-efficacy and physical exercise behaviour. In light of these results, the study recommends strategies aimed at enhancing students' self-efficacy in physical exercise, strengthening social support systems, and improving the exercise environment. This research offers both theoretical insights and empirical evidence to assist universities in formulating effective policies to promote physical exercise among students.